Socialno zavarovanje napotenih delavcev v zakonodaji in sodni praksi EU - Strban, Grega (Delavci in delodajalci, 2018)
Posting of workers between Member States has revived the interest of the legislators, also due to alleged abuses, unfair competition and social dumping. This article is limed to the analysis of social security coordination rules in the EU and does not analyse labour or tax law rules. The conditions of posting, among them activity as an employed person, prior insurance, time restraints and prohibition of chain posting, as well as conditions for effective administrative cooperation, based on Portable Document A1 are scrutinised.
Keywords: applicable legislation; delovno pravo; koordinacija; napotitev; posting; povezovanje sistemov socialne varnosti; Regulation (EC) 883/2004; social security coordination; socialna varnost; Uredba (ES) 883/2004; zakonodaja